2022
DOI: 10.1111/cas.15252
|View full text |Cite
|
Sign up to set email alerts
|

A modified MethyLight assay predicts the clinical outcomes of anti‐epidermal growth factor receptor treatment in metastatic colorectal cancer

Abstract: DNA methylation status correlates with clinical outcomes of anti‐epidermal growth factor receptor (EGFR) treatment. There is a strong need to develop a simple assay for measuring DNA methylation status for the clinical application of drug selection based on it. In this study, we collected data from 186 patients with metastatic colorectal cancer (mCRC) who had previously received anti‐EGFR treatment. We modified MethyLite to develop a novel assay to classify patients as having highly methylated colorectal cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 33 publications
3
24
1
Order By: Relevance
“…Among a total of 15 HMCC cases, 67% (10 cases) had RAS/BRAF mutations, which may have eliminated the significance of DNA methylation status on PFS and OS. In addition, DNA methylation status has been reported to be associated with sensitivity to anti-EGFR antibodies (20)(21)(22)31), but not to chemotherapy (32). Therefore, in the case of HMCC tumors that are sensitive to chemotherapy, therapeutic benefit can be achieved from the chemotherapy with anti-EGFR antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among a total of 15 HMCC cases, 67% (10 cases) had RAS/BRAF mutations, which may have eliminated the significance of DNA methylation status on PFS and OS. In addition, DNA methylation status has been reported to be associated with sensitivity to anti-EGFR antibodies (20)(21)(22)31), but not to chemotherapy (32). Therefore, in the case of HMCC tumors that are sensitive to chemotherapy, therapeutic benefit can be achieved from the chemotherapy with anti-EGFR antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to RAS mutations, the DNA methylation status predicts treatment response to anti-EGFR antibody therapy (19)(20)(21). In a genome-wide DNA methylation analysis in RAS wild-type mCRC, Ouchi et al reported that patients with highly-methylated colorectal cancer (HMCC) are resistant to the anti-EGFR antibody treatment regardless of the primary tumor site (22). Ouchi et al developed a simple method for diagnosing DNA methylation status using the modified MethyLight assay (22).…”
Section: Introductionmentioning
confidence: 99%
“…Ouchi et al reported 16 CpG sites used to determine the genome‐wide DNA methylation status (Table S4 ). 18 Accordingly, we defined the methylation status using these 16 CpG as follows: HMCC, ≥8 methylation‐positive sites; LMCC, ≤7 methylation‐positive sites.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the abovementioned ndings, we developed a novel diagnostic method for GWMS evaluation using the MethyLight assay 27 . To verify the predictive accuracy of this assay, retrospective analyses were performed on patients who received anti-EGFR antibodies as rst-line, secondline, third-line, or later treatment, respectively [27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the abovementioned ndings, we developed a novel diagnostic method for GWMS evaluation using the MethyLight assay 27 . To verify the predictive accuracy of this assay, retrospective analyses were performed on patients who received anti-EGFR antibodies as rst-line, secondline, third-line, or later treatment, respectively [27][28][29] . The results showed that the GWMS classi cation (HMCC or LMCC) using the modi ed MethyLight assay was signi cantly associated with the therapeutic e cacy of anti-EGFR antibodies in all three studies, suggesting its clinical usefulness.…”
Section: Introductionmentioning
confidence: 99%